Model Framework for Analysis and Visualization of Climate Disaster Patterns - Dian Pratiwi (Indonesian Journal on Geoscience, 2022)
DOI:10.17014/ijog.9.3.329-336Extreme climate change has almost begun to show symptoms just about in all countries, including Indonesia. At the beginning of 2020, some parts of Indonesia were flooded due to high rainfall intensity. In fact, in DKI Jakarta area the potential for flooding often arrive early. For this reason, an appropriate disaster pattern analysis system needs to be developed and implemented to prevent the incident from recurring by planning better handling. The model framework that was built to create a visualization system for disaster patterns in this study consisted of five stages, namely the image processing stage in the map image, the placement of the coordinates of the affected area, interpolation with the B-Spline method, extrapolation with the Von-Neumann law, and the accurate evaluation of the formed disaster pattern mapping. Through this model framework, it is expected to produce a system design for informative disaster pattern mapping.